The Impact of IoT-Based Learning on English Proficiency in Civil Engineering Education - Ayu Arisna; Reskyani Anggraeni (Universitas Pahlawan Tuanku Tambusai, 2025)
Civil engineering students frequently struggle to master English in ways that meet professional and technical communication demands. Conventional grammar-focused approaches often fail to provide sufficient relevance to engineering contexts, creating a gap between academic learning and workplace needs. To address this issue, the present study explores the role of the Internet of Things (IoT) in enhancing English learning for civil engineering students. A mixed-methods design was applied, combining a quasi-experimental pre-test and posttest with 60 undergraduate students, analyzed using SPSS, and complemented with questionnaires, classroom observations, and interviews. During the eight-week intervention, students engaged with IoT-based applications such as Duolingo, Cake, Hello English, BBC Learning English, Memrise, and Beelinguapp, as well as cloud-based platforms for collaborative technical writing and sensor-based project simulations that required describing realtime engineering data in English. The results revealed a significant improvement in English proficiency, with post-test scores (M = 72.30) notably higher than pre-test scores (M = 61.20), and a strong correlation (r = 0.721, p 0.05) between IoT use and enhanced vocabulary, writing, and communication skills. Students also reported high engagement, motivation, and satisfaction. The findings suggest that IoT integration is not only effective in improving language proficiency but also provides meaningful, profession-oriented learning experiences that prepare students for global civil engineering communication.